Study on Initial Teacher Education Programme at Secondary Stage - Yadav, S.K. (JOURNAL OF INDIAN EDUCATION, 2011)
The government has initiated several educational measures like District Primary Eduation Programme and Sarva Shiksha Abhiyan. The NCERT provides support and technical assistance to a number of schools in India and oversees many aspects of enforcement of educational policies. The National Policy on Education (NPE) 1986 has provided for environmental awareness, science and technology education introduction of traditional elements and strong teacher’s preparation through preservice and inservice programmes. The National Curriculum Framework 2005 also emphasises that the teachers have the ability to think and take decisions on their own and they can inspire students to be creative and imaginative. The teacher should reflect professionalism in the process of training and teaching. The Teacher training programme should be made strong and thorough review and overhauling of teacher education programmes is required. The study brings about the status of a preservice at secondary stage in India. It also highlights the actions to be taken to strengthen the initial teacher edcuation programme in order to provide quality education at secondary school level across India.